GREEN SYNTHESIS OF SILVER NANOPARTICLES USING SINGLE CELL PROTEIN OF SPIRULINA PLATENSIS - SUGANDHA VERMA; BABITA KUMARI; J.N.SHRIVASTAVA (International Journal of Pharma and Bio Sciences, 2014)
Spirulina platensis, a blue green microalga (cyanobacteria) is used as biologically active food additive and its therapeutic potential is well known, but its property of bioreduction of inorganic material is yet to be exploited.An aqueous solution of silver nitrate was treated with Spirulina powder for the formation of silver nanoparticles. The synthesis of nanoparticles was confirmed by change in color from pale green to reddish brown and Uv-vis absorption peak at 432nm. The size and shape of the nanoparticles were characterized by XRD, FTIR and SEM. The size of nanoparticles was confirmed as 12.77nm using X-ray diffraction analysis.